2009
DOI: 10.1007/s12011-009-8552-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Changes of Trace Elements in Mice Treated with Paradichlorobenzene

Abstract: Paradichlorobenzene (pDCB) has been used as a space deodorant and moth repellant, as well as an intermediate in the chemical industry. Given its broad applications and high volatility, considerable concern exists regarding the adverse health effects of pDCB in the home and the workplace. In this study, changes in lipid peroxidation, antioxidants, and trace element levels in the liver and kidney of pDCB-treated mice were investigated to determine their roles in toxicity. Mice were orally gavaged once daily for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This compound has central nervous system toxicity, causing oxidative damage and trace element alterations in various tissues, as well as oxidative DNA damage, leading to reported cognitive decline. 84,86,87 From our correlation network analysis showing several pathways between chemical biomarkers and cognitive decline, we observed that stroke had relatively strong correlation coefficients with both blood Cd and cognitive decline. This finding highlights the need of this network analysis because blood Cd had protective effects against cognitive decline when considering other identified environmental chemicals in the regression.…”
Section: Discussionmentioning
confidence: 84%
“…This compound has central nervous system toxicity, causing oxidative damage and trace element alterations in various tissues, as well as oxidative DNA damage, leading to reported cognitive decline. 84,86,87 From our correlation network analysis showing several pathways between chemical biomarkers and cognitive decline, we observed that stroke had relatively strong correlation coefficients with both blood Cd and cognitive decline. This finding highlights the need of this network analysis because blood Cd had protective effects against cognitive decline when considering other identified environmental chemicals in the regression.…”
Section: Discussionmentioning
confidence: 84%
“…A carcinogenic mechanism involving metabolism to hydroquinones has therefore been proposed. However, the ability of DCB to induce oxidative stress in vivo has been unclear ( Suhua et al. , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study following inhalation exposure to PDCB for 10 days, researchers found that the concentration of the chemical compound peaked on day 6. The greatest concentration was found to be in adipose tissue, indicating the lipophilic nature of PDCB [Suhua et al 2010]. Oral administration of PDCB in Fischer 344 rats for 28 days showed that the blood plasma concentration peaked on the third day.…”
Section: Pharmacokinetics Of Pdcbmentioning
confidence: 99%
“…Alteration in levels of zinc, selenium and iron were also noted [Weintraub et al 2000]. This study suggested oxidative damage and alteration of trace elements in different tissues as the cause of toxicity [Suhua et al 2010]. Another study showed that some metabolites of PDCB – 2,5-DCHQ and 2,5-dichloro- p -benzoquinone (DCBQ) – can cause oxidative DNA damage in the presence of Cu( II ) and nicotinamide adenine dinucleotide (NADH) [Oikawa and Kawanishi, 1996].…”
Section: Mode Of Pdcb Toxicitymentioning
confidence: 99%